Validity And Reliability of the Indonesian Version of the Kidscreen-52 Questionnaire in Overweight Adolescents - Natalia, Vinda; Pamungkasari, Eti Poncorini; Sari, Yulia (Indonesian Journal of Global Health Research, 2024)
Overweight is one of the health problems that need attention at various ages. Overweight is not only a health problem that is only experienced by adults, but overweight can also occur in adolescence. In adolescents, overweight can also lead to various health problems that can affect quality of life. Objective: Given the importance of quality-of-life issues in overweight adolescents, this study aims to adapt and validate the Kinderscreen-52 questionnaire. Method: This study is a quantitative study with a cross-cultural approach to instrument adaptation and validation. The stages of the process of translating the Kinderscreen-52 instrument into Indonesian adopted Brislin's (1970) procedure in Astuti & Kao (2022), it is translation and back translation. The population involved in the validation of the Indonesian version of the Kinderscreen-52 instrument is overweight adolescents, aged 16-18 years who attend school in the city of Semarang. Results: The results of the Content validity index (I-CVI) by three experts obtained a value of 1 which means valid and the results of the instrument trial obtained reliability with Cronbach alpha 0.748. Conclusions: The Indonesian version of the Kidscreen-52 instrument has gone through appropriate procedures in the cross-cultural adaptation and validation process with good validation and reliability results.